Evaluation of browning rate of quince at ambient exposure - Guiné, Raquel (2012)
Since quince is a fruit relatively susceptible to browning, in the present work it was evaluated the colour of the quince over time of exposure to the atmospheric air. The colour of the fresh pulp was assessed using a handheld tristimulus colorimeter using the CIELab colour coordinates: L*a*b*. These Cartesian coordinates were then used to calculate the polar or cylindrical coordinates: value, hue angle (º) and chroma. At each instant, ten measurements of colour were made, and to evaluate the colour change, measurements were repeated in the same samples after every 5 minutes, over a period of two hours. The results obtained for the medium values of the cylindrical coordinates in the freshly cut quince were found to be: value = 7.80, chroma = 31.78 and Hue = 92.28º, being these values determined right after cutting. Total colour difference (TCD) was calculated having the values of the Cartesian coordinates of the freshly cut quince as reference. In relation to the colour change, the values for TCD were 0.00, 26.35, 30.41, 31.81 and 32.39, respectively for times 0, 30, 60, 90 and 120 minutes, indicating a faster rate initially and a tendency for stabilization towards the end of the period analyzed.